2019
DOI: 10.1371/journal.pone.0216288
|View full text |Cite
|
Sign up to set email alerts
|

Public speaking anxiety decreases within repeated virtual reality training sessions

Abstract: Therapy for public speaking phobia using virtual reality exposure (VRE) has focused on distress arousal rather than distress habituation. Understanding habituation will help optimise session duration, making treatment more affordable and accessible. This pilot study utilised within-speech repeated measures to examine distress habituation during three brief public speaking scenarios in a non-clinical sample ( n = 19; 18–76 years). VRE elicited significant distress in all three scenarios. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 36 publications
0
32
0
4
Order By: Relevance
“…In addition to the wealth of experimental support for this approach over habituation (Craske et al, 2014) -although challenged by recent research (Scheveneels et al, 2019)-this decision was also based on a hypothesis, supported by the physiological findings from the pilot replication study in adolescents (Kahlon et al, 2019), that the VR public speaking paradigm would not evoke a physiological response on par with real-life public speaking, even among users with severe PSA. While previous research has shown that VR public speaking does evoke a significant physiological and subjective fear response, this response is small in terms of absolute numbers (Owens & Beidel, 2015;Takac et al, 2019) and lower than that observed in for example PTSD (Rauch et al, 2018). Arguably, this contrast is due both to the complexity of presenting human stimuli from a graphical perspective (Seyama & Nagayama, 2007), and that many of the most common catastrophic beliefs related to public speaking concern perception by others (Stein et al, 1996), which may be hard to evoke when the user knows that the audience are not real people.…”
Section: Discussionmentioning
confidence: 90%
“…In addition to the wealth of experimental support for this approach over habituation (Craske et al, 2014) -although challenged by recent research (Scheveneels et al, 2019)-this decision was also based on a hypothesis, supported by the physiological findings from the pilot replication study in adolescents (Kahlon et al, 2019), that the VR public speaking paradigm would not evoke a physiological response on par with real-life public speaking, even among users with severe PSA. While previous research has shown that VR public speaking does evoke a significant physiological and subjective fear response, this response is small in terms of absolute numbers (Owens & Beidel, 2015;Takac et al, 2019) and lower than that observed in for example PTSD (Rauch et al, 2018). Arguably, this contrast is due both to the complexity of presenting human stimuli from a graphical perspective (Seyama & Nagayama, 2007), and that many of the most common catastrophic beliefs related to public speaking concern perception by others (Stein et al, 1996), which may be hard to evoke when the user knows that the audience are not real people.…”
Section: Discussionmentioning
confidence: 90%
“…On the other hand, the level of interactivity that 3D scenarios offer can be very useful in applied research, since they display more naturalistic and interactive environments, facilitating decision-making research and the analysis of daily situations. Taking some examples, Takac et al [ 137 ] analysed the anxiety felt by speakers when faced by large audiences, Lin et al [ 133 ] analysed the stress felt by individuals when in a building on fire scenario and Kisker et al [ 130 ] analysed arousal in an exposure to a high height.…”
Section: Discussionmentioning
confidence: 99%
“…Among the virtual environments generated with VR, most researches recreated a virtual classroom and an auditorium with a fictitious audience [20,21]. In addition, other studies virtualized everyday situations, which were made possible by the realism of the interactions [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 360º recording technology generates virtual environments with greater realism [8]. These environments are so real that some studies claim that virtual spectators in a classroom can affect people's beliefs, anxiety, and behavior [7,22,23]. Unlike in vivo exposure techniques, VR generates virtual environments that favor privacy, avoid public embarrassment, and maintain patient confidentiality [24].…”
Section: Introductionmentioning
confidence: 99%